Internalization Methods Multicultural Value in Early Childhood Education - Kasmiati Kasmiati (STAI Hubbulwathan Duri, 2023)
Multiculural values are one of the important values that should be taught in early childhood, with the aim that children can coexist and tolerate with various differences. The purpose of this study was to find and clarify the presentation of facts related to effective methods in internalizing multicultural values in early childhood with case studies in PAUD Karuna Dipa Palu. This type of research is qualitative research, data collection is carried out by means of observation, interviews and documentation. Data analysis is carried out by means of reduction, data presentation, verification and drawing conclusions. The success of building a harmonious life is inseparable from the development of learning method based on internalizing multicultural values organized with four main methods: (1) contributive method in learning that gives teachers the role to be directly involved in selecting the source, language, material, and theme taught are designed to convey multicultural values in the context of the environment around the learners; (2) additive method carried out in providing additional completeness of learning so that learning activities are more effective in internalizing multicultural values in early childhood; (3) social transformation method is carried out in order to conditioning learners to practice multicultural values through social interaction; and (4) social action method performed by the direct casting of children's social actions in various activities that represent the multicultural understanding of early childhood.